Penal theories and institutions lectures at the Collège de France, 1971-1972 - Foucault, Michel 1926-1984 (Picador, 2021)
"The thirteenth and final English volume of Michel Foucault's Lectures at the Collège de France"--
Includes bibliographical references and index
Keywords: Foucault, Michel -- 1926-1984; Collège de France; Staat; Unterdrückung; Vorlesung; Macht; Criminal justice, Administration of / France / History; Law / Political aspects; Justice (Philosophy); Power (Philosophy)